2014
DOI: 10.1007/978-1-4471-6524-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Speaker Recognition Anti-spoofing

Abstract: Progress in the development of spoofing countermeasures for automatic speaker recognition is less advanced than equivalent work related to other biometric modalities. This chapter outlines the potential for even state-of-the-art automatic speaker recognition systems to be spoofed. While the use of a multitude of different datasets, protocols and metrics complicates the meaningful comparison of different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…The EERs of CQCC [7] and CQCC-A [7] are taken from [7]. Earlier work [1][2][3] on spoofing detection showed that phase related features perform better than amplitude-based features. This is because natural phase information is almost entirely lost in spoofed speech realized using voice conversion and speech synthesis approaches [1][2][3].…”
Section: Performance Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…The EERs of CQCC [7] and CQCC-A [7] are taken from [7]. Earlier work [1][2][3] on spoofing detection showed that phase related features perform better than amplitude-based features. This is because natural phase information is almost entirely lost in spoofed speech realized using voice conversion and speech synthesis approaches [1][2][3].…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Earlier work [1][2][3] on spoofing detection showed that phase related features perform better than amplitude-based features. This is because natural phase information is almost entirely lost in spoofed speech realized using voice conversion and speech synthesis approaches [1][2][3]. It is observed from the results of tables 2 that amplitude-based features (e.g., LFCC, CQCC, and IQCC) can provide better or at least comparable results to that of the phase related features.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Impostors may change phonation by using glottal fry or whisper voice; change pitch; change accents by using a foreign accent or another dialect; or do anything else in their power to hide their identities. Especially in forensics, the importance of awareness of voice disguise has been emphasised since the 1970s [1][2][3][4][5][6][7][8][9][10]. In the last two decades, researchers have warned of a new type of voice disguise, the use of synthetic speech [11][12][13].…”
Section: Introductionmentioning
confidence: 99%